Two new species of Plagiostomum (Prolecithophora, Plagiostomidae) from China with its morphology, phylogeny, and reproductive strategy - Leyuan Feng; Shiyan Zhang; Ming Tao; Ting Sun; Antai Wang (Frontiers in Marine Science)
Plagiostomum flatworms are small, free-living organisms frequently found in saltwater or freshwater habitats, but their biological characteristics remain largely unknown. Here, we describe two new species of Plagiostomum collected from the intertidal zone of the South China Sea, based on the integrative studies of morphology, phylogeny, reproduction, and juvenile development. Morphologically, Plagiostomum nanhaiensis sp. nov. can be distinguished from congeneric species by its three dark brown dorsal stripes, pear-shaped vesicula seminalis located ventrally to the intestine, and the testes surrounding the ovaries and bead-like sperm. Additionally, Plagiostomum plagae sp. nov. can be distinguished from P. nanhaiensis sp. nov. and other congeneric species by its two connected dorsal stripes, multiple spherical testes arranged along the ventral midline, a hemispherical vesicula seminalis located on the right ventral side, and grain-shaped sperm. Kimura’s two-parameter distance and phylogenetic analyses further support the recognition of these two new species, showing that the three specimens of P. nanhaiensis sp. nov. and P. plagae sp. nov. form two separate clades within Plagiostomum with solid support. Moreover, these two new species exhibit similar habits and reproductive strategies, adopting hypodermic impregnation. The reproductive studies indicate that in natural environments or larger mating groups, these two new species tend to invest resources in male reproductive functions to enhance fertilization success, while in smaller or single-individual cultures, they shift resources toward complete female reproductive functions. Our results not only enrich the biodiversity data of the family Plagiostomidae in China but also provide new empirical evidence for existing sex allocation theories.